Cholesterol concentrations in lipoprotein fractions separated by anion-exchange–high-performance liquid chromatography in healthy dogs and dogs with hypercholesterolemia. (October 2017) - Oda, Hitomi; Mori, Akihiro; Hirowatari, Yuji; Takoura, Toshie; Manita, Daisuke; Takahashi, Tomoya; Shono, Saori; Onozawa, Eri; Mizutani, Hisashi; Miki, Yohei; Itabashi, Yukiko; Sako, Toshinori
Abstract: Anion-exchange (AEX)–high-performance liquid chromatography (HPLC) for measurement of cholesterol can be used to separate serum lipoproteins (high-density lipoprotein (HDL); low-density lipoprotein (LDL); intermediate-density lipoprotein (IDL); very-low-density lipoprotein (VLDL)) in humans. However, AEX–HPLC has not been applied in veterinary practice. We had three objectives: (i) the validation of AEX-HPLC methods including the correlation of serum cholesterol concentration in lipoprotein fraction measured by AEX–HPLC and gel permeation–HPLC (GP–HPLC) in healthy dogs and those with hypercholesterolemia was investigated; (ii) the reference intervals of lipoprotein fractions measured by AEX–HPLC from healthy dogs (n = 40) was established; (iii) lipoprotein fractions from the serum of healthy dogs (n = 12) and dogs with hypercholesterolemia (n = 23) were compared. Analytic reproducibility and precision of AEX–HPLC were acceptable. Positive correlation between serum concentrations of total cholesterol (Total-Chol), HDL cholesterol (HDL-Chol), LDL cholesterol (LDL-Chol) + IDL cholesterol (IDL-Chol), and VLDL cholesterol (VLDL-Chol) was noted for AEX–HPLC and GP–HPLC in healthy dogs and dogs with hypercholesterolemia. Reference intervals measured by AEX–HPLC for serum concentrations of Total-Chol, HDL-Chol, and LDL-Chol were determined to be 2.97–9.32, 2.79–6.57, 0.16–3.28 mmol/L (2.5–97.5% interval), respectively. Furthermore, there was significant difference in lipoprotein profiles between healthy and dogs with hypercholesterolemia. These results suggest that AEX–HPLC can be used to evaluate lipoprotein profiles in dogs and could be a new useful indicator of hyperlipidemia in dogs. Highlights: Anion-exchange high-performance liquid chromatography (AEX–HPLC) for lipoprotein analysis was evaluated in dogs. Analytic reproducibility and precision of AEX–HPLC were acceptable in dogs. Reference intervals of lipoprotein measured by AEX–HPLC were established in dogs. There is significant difference in lipoprotein profiles between healthy and hypercholesterolemia dogs. AEX–HPLC can be used to evaluate lipoprotein profiles in dogs.